Green management and green technology - exploring the causal relationship - Jazmin Seijas Nogareda; Andreas Ziegler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
In this paper, we analyze potential endogeneity problems in former econometric studies which regress corporate environmental performance such as green technology activities on green management. Based on evolutionary theory and the resource-based view of the firm, we discuss in the first step that green technology could also influence green management and that unobserved firm characteristics could simultaneously influence green management and green technology. Contrary to existing studies, we empirically explore in the second step the structural reverse causality hypothesis with a unique crosssectional firm-level data set from the German manufacturing sector. Our econometric analyses with uni- and multivariate probit models imply a significantly positive effect of environmental process innovations on certified environmental management systems and a significantly positive impact of environmental product innovations on life cycle assessment activities. We interpret these empirical results as a further indicator that the causal relationship between green management and green technology is not clear. We conclude that panel data, which are not available for technological environmental innovations yet, are a necessary condition to solve these endogeneity problems. Such panel data studies could therefore be an appropriate basis for robust conclusions with regard to voluntary green management measures as a non-mandatory approach in environmental policy.
Keywords: 330; Non-mandatory environmental policy; green management; green technology; uni- and multivariate probit models; endogeneity